FAKTOR LINGKUNGAN DAN PERILAKU KEJADIAN LEPTOSPIROSIS DI KOTA SEMARANG - Nurulia Unggul Putri Ragil; Budiyono Budiyono; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2016)
Leptospirosis is a bacterial disease caused by Leptospira sp. Leptospirosis cases in Semarang in 2013 were 70 cases with 11 were died and it was increase in 2014 there were an 75 cases with 13 were died. This study aims to determine the environmental and behavioral risk factors associated with the incidence of leptospirosis in five working areas of the health centers. This research is observational with case-control study design. The sample of the research consisted of 50 respondents from 25 case respondents and 25 control respondents. The primary data collecting from interviews and observations with the respondents. The installment of rats trapping has been done to identify the existence of rats around homes of the respondents and water sampling has done too for testing the existence of Leptospira sp. in the environtment. Data analysis consist of univariate analysis and biavariat analysis. The results showed that 14 (56%) of respondents cases which presence of puddle around their homes and have a history of injuries. One of the 15 water samples tested showed positive result (+) Leptospira sp.The results showed that there is an association between a history of wounds to the incidence of Leptospirosis with p = 0.001 (p≤0,05) and variable presence of puddle (OR = 3.273 95% CI = 1.008 to 10.621) and history of wounds (OR = 2.820 95% CI = 2.820 to 75.954) are risk factors of leptospirosis. So the presence of puddle and a history of wounds are environmental and behavioral risk factors for the leptospirosis cases in the Semarang.